Corrigendum to "Aerosol properties associated with air masses arriving into the North East Atlantic during the 2008 Mace Head EUCAARI intensive observing period: an overview" published in Atmos. Chem. Phys., 10, 8413-8435, 2010 - M. Dall'Osto; D. Ceburnis; G. Martucci; J. Bialek; R. Dupuy; S. G. Jennings; H. Berresheim; J. C. Wenger; R. M. Healy; M. C. Facchini; M. Rinaldi; L. Giulianelli; et al. (Atmospheric Chemistry and Physics, 2010)
No abstract available.